Screening of wheat germ plasm for resistance to Microdochium nivale under field conditions - C. Eken; S. Bulut; A. Öztürk; E. Dane; Ö. Cağlar; E. Demireci (Journal of Animal and Plant Sciences, 2011)
Pink snow mold, caused by Microdochium nivale, is a serious disease of winter wheat (Triticum aestivum) in the Northern Hemisphere. A field study with artificial inoculation was conducted using 38 winter wheat cultivars during the 2002-2003 at Erzurum, Turkey. Significant differences were detected among cultivars for reaction and yield components to the M. nivale. The most resistant winter wheat cultivars were Harmankaya and Pehlivan, and the most susceptible ones were Aytin-97, Kırgız-95 and Bayraktar. Yield components decreased significantly in inoculated plants. Pink snow mold resulted in decreased number of spikes per m2, the grain yield and the plant height of 71.1, 67.3 and 13.2% respectively.
Keywords: Triticum aestivum; pink snow mold; yield components; Microdochium nivale